FLO Genes Family and Transcription Factor MIG1 Regulate Saccharomyces cerevisiae Biofilm Formation During Immobilized Fermentation - Yang, Leyun; Zheng, Cheng; Chen, Yong; Ying, Hanjie (Frontiers in Microbiology, 2018)
Saccharomyces cerevisiae immobilization is commonly used for efficient ethanol fuel production in industry due to the relatively higher ethanol stress resistance of S. cerevisiae in biofilms relative to planktonic cells. The mechanisms of biofilm formation and stress resistance, however, remain ambiguous. By analyzing biofilm and planktonic cell transcriptomes, this study observed that MIG1 (encoding a transcription factor) expression in cells increases during the biofilm formation process. To identify the role of MIG1 in yeast biofilm formation and the ethanol resistance of these cells, MIG1 was deleted and complemented in S. cerevisiae 1308. Results showed the MIG1 deletion mutant strain demonstrated weaker biofilm formation ability both on fibers and plastic than the wild-type and these could be restored by expressing MIG1 in deletion mutant. To verify the ability of MIG1 to regulate the expression of FLO genes, which encode adhesions responsible for yeast biofilm formation, FLO gene transcription levels were measured via qRT-PCR. Relative to wild-type S. cerevisiae, the adhesion genes FLO1, 5, and 9 which also demonstrate increased expression in the transcriptome of yeast cells during biofilm formation, but not FLO11, were down-regulated in the MIG1 mutant strain. Additionally, the MIG1 mutant lost a majority of its flocculation ability, which depended on cell-cell adhesions and its slightly invasive growth ability, dependent on cell-substrate adhesion. Deleting FLO1, 5, and 9 decreased biofilm formation on plastics, suggesting these FLO genes contribute to the biofilm formation process alongside FLO11. Moreover, the ethanol tolerance of yeast decreased in the MIG1 deletion mutant as well as the FLO11 deletion mutant, resulting in reduced biofilm formation during fermentation. It remains possible that in the later period of fermentation, when ethanol has accumulated, an over-expression of the FLO1, 5, and 9 genes regulated by MIG1 would enhanced cell-cell adhesions and thus protect cells in the outer layer of biofilms from ethanol, a function primarily dependent on cell-cell adhesions. This work offers a possible explanation for how biofilm formation is regulated during the immobilized fermentation process, and can enhance environmental tolerance in industrial production.